Паразитические черви пастушков (Ralli) и куликов (Limicolae) бассейна Верхнего Днестра - Сергиенко, М.И. (Вестник зоологии, 1972)
123 birds — representatives of 12 species were examined by means of complete helminthological dissection. In Ralli 25 species of helminths were found. Extensivenes of infestation was 90.6%. High extensiveness of infestation was observed during invasion with Prosthogonimus ovatus (30.0%), Tetrameres fissispina (34.0%), Filicollis anatis (36.3%) which are of epizootological significance. In Limicolae 19 species of parasitic worms were registered. Infestation extensiveness was 95.8%. Among helminths found in Limicolate there is a small number of agents of serious diseases.